UPAYA PENINGKATAN PENGETAHUAN DAN KETERAMPILAN MENJAGA KESEHATAN GIGI DAN MULUT PADA ANAK USIA DINI - Jannah, Fitriatul; Istiana, Dina; Jeje, Riska (PPM STIKES Adi Husada, 2026)
Introduction & Aim: Oral and dental health problems among early childhood remain high, as indicated by the high prevalence of dental caries among children in Indonesia. The low level of proper toothbrushing behavior is one of the main contributing factors. This community service activity aims to improve the knowledge and skills of kindergarten children in maintaining oral and dental health, as well as to promote healthy habits from an early age. Method of Activity: The activity was conducted in the form of health promotion through education, simulation, and question-and-answer sessions. The strategies included: (1) delivering educational materials on oral and dental health, (2) using PowerPoint and animation media to attract children’s attention, (3) conducting simulations using dental mannequins as practical tools, (4) demonstrating proper toothbrushing techniques accompanied by educational songs, and (5) evaluating participants through direct observation of their understanding and participation. The target participants were 95 students of TK Kuncup Harapan. Results: The activity involved 95 students divided into two sessions. The results showed that the students understood the material and were able to demonstrate proper toothbrushing techniques. All participants showed high enthusiasm during the simulation and interactive activities. Discussion: This health promotion activity was effective in improving children’s knowledge and skills regarding oral and dental care. The use of interactive educational methods, such as animation and simulation, proved to enhance children’s participation. This activity also serves as a preventive effort to reduce the risk of dental caries and to support the improvement of children’s health status from an early age.